The Role of IL-25 and IL-35 in Amoebiasis (Indian Journal of Forensic Medicine & Toxicology, 2020)
Bacground: Amoebiasis is a protazon infection of the human intestine spread through the world the mostprevelant form of the disease is amebic dysenterywhich characterizes acute diarrhoea with observable bloodand mucus in stools.Aims: This article aimed to detects the role of IL-25 and IL-35 in the immune response against amebicdysentery.Methods: This study was conducted in Thi-Qar province-Al-Nasiriyah city in Muhammad Al-MousawiHospital for Children, the study included collection of (60)blood samples from amebiasis patients and (30)apparently healthy children at a period from September 2019 to March 2020 with the age less than oneyear to 15 years that divides to four age groups, the levels of IL-25 and IL-35 were determined by ELISAtechnique.Results:The results indicate that the IL-25 and IL-35 concentrations in serum samples from amoebiasispatients were significantly higher when compared with that from healthy controls. The highest level of IL-25was recordsin the third age group of patients with level 1677.2 ± 867.2ng /ml,compare with the high level inthe third age group of control with level 450.40 ± 97.31ng /ml.Also, the findings indicates the highest levelof IL-35 records35 in the second age group of patients with level 291.0 ± 62.3ng /ml, while the high levelrecorded in the first age group of control with level 8.246± 0.60 ng /ml.
Keywords: IL-25, IL-35, Amoebiasis, cytokine